Prokaryotic diversity and community structure in the rhizosphere of Lantana weed (Lantana camara L.) - Gola, Upasana; Kour, Shilippreet; Kaur, Tanvir; Perveen, Kahkashan; Bukhari, Najat A.; Alsulami, Jamilah A.; Maithani, Damini; Dasila, Hemant; Singh, Manali; Suyal, Deep Chandra (Frontiers in Plant Science, 2023)
Lantana weed (Lantana camara L.) is among the most noxious weeds in the world. Keeping in mind its invasive behavior and great ecological tolerance, it becomes imperative to analyze the structure and function of associated microbiome. In this perspective, Illumina-based metagenome sequencing of a composite soil sample was performed to gain a better understanding of prokaryotic diversity and community structure in the rhizosphere soil. The organic carbon, nitrogen, phosphorus, and potassium contents in the rhizosphere soil were 0.91 % (± 0.21 %); 280 Kg ha-1 (± 4.02 Kg ha-1), 54.5 Kg ha-1 (± 3.12 Kg ha-1), and 189 Kg ha-1 (± 6.11 Kg ha-1), respectively. The metagenome analysis revealed the existence of 41 bacterial and 2 archaeal phyla, with only 12 showing ≥1% abundances. Pseudomonadota was the dominant phylum with 31.3% abundance, followed by Actinomycetota (20.9%). Further, 54 different genera were identified with the highest abundance of Devosia (2.8%). The PICRUSt analysis predicted various functional traits in the soil metagenome, with general cellular functions dominating, followed by stress tolerance. Moreover, 10% of the functions were associated with nitrogen fixation, phosphate solubilization, and potassium mobilization. In conclusion, the present study revealed the existence of diverse prokaryotic communities in the rhizosphere of the Lantana camara L. which was primarily associated with stress response and plant growth promotion. To the best of our knowledge, this study documents for the first time the Lantana camara L. microbiome. Furthermore, the identified genera can be explored for agricultural needs in future.